Penyuluhan Hukum Mengenai Omnibus Law Undang-Undang Cipta Kerja kepada Pekerja PT Sucofindo Cabang Pekanbaru - Andrew Shandy Utama (COMSEP: Jurnal Pengabdian Kepada Masyarakat, 2021)
This community service activity aims to provide legal education to employees of PT Sucofindo Pekanbaru Branch regarding the Omnibus Law of the Job Creation Act. The method of implementation used in this community service activity is to use the lecture method as well as dialogue and discussion. This community service activity was carried out on Wednesday, December 30, 2020 at 13.00 WIB until it was finished at the Ayam Remuk Pak Tisto Restaurant, which is located at Yos Sudarso Street, Rumbai Pesisir District, Pekanbaru City. This community service activity was attended by 17 (seventeen) workers of PT Sucofindo Pekanbaru Branch. The conclusion is that this community service activity has been successful. From the questionnaires given before the activity started, only 43.5% of participants were able to answer correctly. Meanwhile, after the activity was completed, 84.7% of participants managed to answer correctly.